Building a Floating Hydroponic Garden - Michael Sweat; Richard Tyson; Robert Hochmuth (EDIS)
The Aztecs and Incas amazed the Spanish conquistadors with their floating gardens, and now, 500 years later, you can impress your friends and neighbors with yours. A floating hydroponic garden is easy to build and can provide a tremendous amount of nutritious vegetables for home use. Best of all, hydroponic systems avoid pest problems commonly associated with the soil. This simple guide will show you how to build your own floating hydroponic garden using locally available material for about $50.00.